Modelling of single bubble-dynamics and thermal effects. (November 2015) - Papoulias, D; Gavaises, M
Abstract: This paper evaluates the solution effects of different Rayleigh-Plesset models (R-P) for simulating the growth/collapse dynamics and thermal behaviour of homogeneous gas bubbles. The flow inputs used for the discrete cavitation bubble calculations are obtained from Reynolds-averaged Navier-Stokes simulations (RANS), performed in high-pressure nozzle holes. Parametric 1-D results are presented for the classical thermal R-P equation [1] as well as for refined models which incorporated compressibility corrections and thermal effects [2, 3]. The thermal bubble model is coupled with the energy equation, which provides the temperature of the bubble as a function of conduction/convection and radiation heat-transfer mechanisms. For approximating gas pressure variations a high-order virial equation of state (EOS) was used, based on Helmholtz free energy principle [4]. The coded thermal R-P model was validated against experimental measurements [5] and model predictions [6] reported in single-bubble sonoluminescence (SBSL).